Saluto e introduzione alle giornate di studio (Materiali di Estetica. Terza serie, 2020)
As Director of the Department of Philosophy, Sociology, Pedagogy and Applied Psychology, in which we can find the heritage of Dino Formaggio, I should like to remember, first of all, his relevant contributions to build up a new way in the field of the studies in Aesthetics in Italian culture, but also his strong commitment in the political and civil debate during his life, and, last but not least, his work as an original artist. It is a very important heritage, which we have always to remember.
Keywords: Aesthetics; Political and Civil Commitment; Artistic Work; Heritage